Prayer and poetry in the Dead Sea Scrolls and related literature: essays on prayer and poetry in the Dead Sea scrolls and related literature in honor of Eileen Schuller on the occasion of her 65th birthday - Wassen, Cecilia; Schuller, Eileen M.; Penner, Jeremy; Penner, Ken M. (Studies on the texts of the desert of Judah, 2012)
A timely collection of contributions by major scholars in the field of prayer and poetry in the Dead Sea Scrolls